Analysis of Antenatal Care Service Coverage at Public Health Centers in Agam Regency - Bismihayati Bismihayati; Abdul Razak; Eri Barlian; Nurhasan Syah; Syafrijon Syafrijon (Science and Environmental Journal for Postgraduate, 2021)
Reducing maternal mortality is one of Indonesia's main targets for improving health. By offering antenatal care services for pregnant women at least four times with the standard 10T during pregnancy, efforts are made to reduce maternal mortality. This kind of research uses a phenomenological approach and is qualitative in nature. The purpose of this study is to obtain, obtain a description, analysis, interpretation of the coverage of antenatal care services. Data were obtained from in-depth interviews with 20 informants consisting of the head of the Puskesmas, Coordinator Midwife, Village Midwife, Cadre and pregnant women. The study findings indicate that although antenatal care services at the Agam District Health Center are covered, the policy reference to Minimum Service Standards has not been met in terms of facilities, labor, or funding. The author suggests expanding the access of pregnant women to health workers through the "Ojol for Pregnant Women" activity, because it is concluded that the coverage of antenatal care services at the Agam District Health Center has not reached the Minimum Service Standards and is expected to improve services, especially visits to pregnant women, health education, and improvement of health services. community participation. This activity is in the form of transportation prepared by the community, either two-wheeled or four-wheeled vehicles that are ready to pick up pregnant women to health facilities